15-n7=13

Subtract 15 from both sides of the equation.

-n7=13-15

Subtract 15 from 13.

-n7=-2

-n7=-2

Multiply both sides of the equation by -7.

-7⋅(-n7)=-7⋅-2

Simplify -7⋅(-n7).

Cancel the common factor of 7.

Move the leading negative in -n7 into the numerator.

-7⋅-n7=-7⋅-2

Factor 7 out of -7.

7(-1)⋅-n7=-7⋅-2

Cancel the common factor.

7⋅-1⋅-n7=-7⋅-2

Rewrite the expression.

-1⋅(-n)=-7⋅-2

-1⋅(-n)=-7⋅-2

Multiply.

Multiply -1 by -1.

1⋅n=-7⋅-2

Multiply n by 1.

n=-7⋅-2

n=-7⋅-2

n=-7⋅-2

Multiply -7 by -2.

n=14

n=14

Solve for n 15-n/7=13